Student-perceived exam difficulty may trump the effects of different quality improvement measures regarding the students’ evaluation of a pediatric lecture series - Marco S. Spehl (BMC Medical Education, 2019)
Abstract Background Lectures are still an important part of today’s medical education at many medical schools. The pediatric lecture series at the Center for Pediatrics, Medical Center, University of Freiburg, Faculty of Medicine, University of Freiburg, Germany had been evaluated poorly in recent terms. Methods To improve lecture quality and possibly evaluation results a combination of measures consisting of peer lecturer coaching, use of an audience response system, in depth analysis of the end of term evaluation results and changes to the exam itself were implemented. Results Peer lecturer coaching was performed successfully and both the audience response system evaluation as well as the end of term evaluation results improved significantly in the following term. Analysis of the students’ comments revealed more approval of lecture content and presentation after the organization of the lecture series was changed towards less lecturers and focus on less topics. Student-perceived high exam difficulty influenced the evaluation negatively. Conclusion The student-perceived exam difficulty can supersede the effects of different measures to improve lecture quality measured via evaluation. Whether better evaluation of the lecture series after different improvement measures was due to better match of the curriculum with the exam content or that an improved curriculum led to better exam performance remains to be elucidated.